Engaging EFL Students in English Phrases of Academic Writing: How and Why? - Sri Wahyuningsih (Universitas Muria Kudus, 2021)
Academic writing has played a significant role for academicians including EFL students in academic context. Indeed, it needs study and practice to upgrade this skill since academic writing is not really easy particularly for novice writers. This paper reports the importance of engaging EFL students in English phrases of academic writing to help them improve their academic works. Further, this study reports the EFL students’ responses to the practice of English academic phrases. This study anchors in a qualitative research. Data were garnered through in-depth interviews to ten students of English Department at Institut Agama Islam Negeri Kudus. Besides, a documentation was conducted to enhance their academic writing works. The results revealed that engaging EFL students in English phrases of academic writing has been beneficial for introducing work, referring to literature, describing methods, reporting results, discussing findings, and writing conclusions. Further, they become more familiar with a number of English phrases used in academic writing. Importantly, they become more encouraged to write academic papers and improve their publication.